Nipple Sparing Mastectomy: Does Breast Morphological Factor Related to Necrotic Complications? - Chirappapha, Prakasit; Petit, Jean-Yves; Rietjens, Mario; De Lorenzi, Francesca; Garusi, Cristina; Martella, Stefano; Barbieri, Benedetta; Gottardi, Alessandra; Andrea, Manconi; Giuseppe, Lomeo; Hamza, Alaa; Lohsiriwat, Visnu (Plastic and reconstructive surgery. Global open, 2014)
BACKGROUND:Nipple sparing mastectomy (NSM) can be performed for prophylactic mastectomy and the treatment of selected breast cancer with oncologic safety. The risk of skin and nipple necrosis is a frequent complication of NSM procedure, and it is usually related to surgical technique. However, the role of the breast morphology should be also investigated. METHOD:We prospectively performed an analysis of 124 NSM from September 2012 to January 2013 at the European Institute of Oncology, Milan, Italy, focusing on necrotic complications. We analyzed the association between the risks of skin necrosis and the breast morphology of the patients. RESULTS:Among 124 NSM in 113 patients, NSM procedures were associated with necrosis in 22 mastectomies (17.7%) among which included partial necrosis of nipple-areolar complex (NAC) in 15 of 124 NSM (12.1%) and total necrosis in 4 cases (3.5%). The NAC was removed in 5 NSM cases (4%). The volume of breast removed was the only significant factor increasing the risk of skin necrosis. The degree of ptosis was not significantly related to the necrosis risk. CONCLUSIONS:Large glandular specimen increases the risk of NAC necrosis. The degree of ptosis and the distance between the sternal notch and the NAC have no significant impact on necrotic complications in NSM. To reduce the necrotic complications in large breast after NSM, reconstruction should better be performed with autologous flap or slow skin expansion using the expander technique.